Understanding user reactions and interactions with an internet-based intervention for tinnitus self-management: mixed-methods process evaluation protocol - Greenwell, Kate; Sereda, Magdalena; Coulson, Neil S.; Hoare, Derek J. (JMIR Publications, 2016)
Background: Tinnitus is a common medical symptom that can affect an individual’s emotional and functional quality of life. Psychological therapies are acknowledged as beneficial to people with tinnitus; however, such therapies are not always readily accessible. With their global reach, automated Internet-based interventions have the potential to reduce the disparity in access to psychological support that people with tinnitus currently experience. However, the evidence on the acceptability and efficacy of these interventions is lacking. Process evaluations that develop an in-depth understanding of how users experience these interventions provide an essential first step when evaluating complex psychological interventions. Objective: To describe the protocol for a study that will explore past, current, and new users’ reactions to and interactions with the Tinnitus E-Programme, an Internet-based intervention for the self-management of tinnitus. Methods: Two parallel mixed-methods studies will be carried out with 2 different populations. Study 1 will use an online survey to gather past and current users’ views of the program. Study 2 will recruit new program users to take part in an interview and complete a relaxation log to explore how well they were able to implement the skills they learned during the program in their everyday lives. The findings from both studies will be triangulated to develop an in-depth understanding of the program’s mechanisms of impact and identify any implementation or contextual factors that strengthen or impede its delivery and functioning. Results: Study 1 is open for recruitment with a projected completion in June 2016 and Study 2 was completed November 2015. At the time of submission, 36 participants have been recruited to Study 1 and 12 participants have taken part in Study 2. Conclusions: Findings will inform the optimization of the Tinnitus E-Programme and guide future evaluation work to assess the program’s effectiveness as a therapy for people with tinnitus.